RNase E is required for the maturation of ssrA RNA and normal ssrA RNA peptide-tagging activity - Lin-Chao, Sue (The National Academy of Sciences, 1999)
During recent studies of ribonucleolytic “degradosome” complexes of Escherichia coli, we found that degradosomes contain certain RNAs as well as RNase E and other protein components. One of these RNAs is ssrA (for small stable RNA) RNA (also known as tm RNA or 10Sa RNA), which functions as both a tRNA and mRNA to tag the C-terminal ends of truncated proteins with a short peptide and target them for degradation. Here, we show that mature 363-nt ssrA RNA is generated by RNase E cleavage at the CCA-3′ terminus of a 457-nt ssrA RNA precursor and that interference with this cleavage in vivo leads to accumulation of the precursor and blockage of SsrA-mediated proteolysis. These results demonstrate that RNase E is required to produce mature ssrA RNA and for normal ssrA RNA peptide-tagging activity. Our findings indicate that RNase E, an enzyme already known to have a central role in RNA processing and decay in E. coli, also has the previously unsuspected ability to affect protein degradation through its role in maturation of the 3′ end of ssrA RNA.